ANSWER
A solution of the radical equation that does not satisfy the original radical equation.
Step-by-step explanation
An extraneous is the solution that does not satisfy the original equation.
For instance, given the radical equation:
![√(x + 3) = x - 3](https://img.qammunity.org/2020/formulas/mathematics/high-school/79szjtddhljnh25nn4dr5wxfl2seoca3ax.png)
We square both sides to get:
![{ (√(x + 3) )}^(2) = {(x - 3)}^(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/yk4td0gsb0pzciv5ywa9glu0xbhnz61gac.png)
We expand to get;
![{x + 3} = {x}^(2) - 6x + 9](https://img.qammunity.org/2020/formulas/mathematics/high-school/ijw0dd14blj9vcphmgq9zzznt276uhxqta.png)
We write in standard quadratic forms:
![{x}^(2) - 6x - x + 9 - 3= 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/agnf8ddk3707wgmjlu9udy2njl4ttpi9c8.png)
![{x}^(2) - 7x+6= 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/xrmc21agjajafda790qpk3mpufkorgb6ar.png)
![{(x - 6)(x - 1)} = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/aaieixwgdxpql9v8wgy7yh2eim0wv6zkdh.png)
This implies that;
![x = 1 \: or \: x = 6](https://img.qammunity.org/2020/formulas/mathematics/high-school/4m1ajktupan0fawprc2rgxn2dh9eps008x.png)
When we substitute x= 6 into the equation, we get;
![√(6+ 3) = 6- 3](https://img.qammunity.org/2020/formulas/mathematics/high-school/xvboz20l4uhsz3o0a2pfpwwvybgujv01ix.png)
![√(9) = 3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kob98vxeyblulkkmp3ngrn31l4pf673jl6.png)
This statement is true.
However when we substitute x=1, we get:
![√(1+ 3) = 1- 3](https://img.qammunity.org/2020/formulas/mathematics/high-school/isa2z5zeact5sm9h2mooa4nwm4fywxhlnw.png)
This statement is false.
Hence x=1 u s referred to as an extraneous solution.